2017
DOI: 10.1002/2017wr020459
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Time‐Lapse Gravity Survey and Hydraulic Tomography for Estimating Spatially Varying Hydraulic Conductivity and Specific Yield Fields

Abstract: Hydraulic conductivity (K) and specific yield ( Sy) are important aquifer parameters, pertinent to groundwater resources management and protection. These parameters are commonly estimated through a traditional cross‐well pumping test. Employing the traditional approach to obtain detailed spatial distributions of the parameters over a large area is generally formidable. For this reason, this study proposes a stochastic method that integrates hydraulic head and time‐lapse gravity based on hydraulic tomography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…It can be challenging to map the three‐dimensional function of S y ( x , y , z ) in Equation considering aquifer heterogeneity and the high cost of conducting pumping tests over different depths, despite some successes reported in the literature (Tsai et al, 2017; Yeh & Liu, 2000; Zhu & Yeh, 2005). Furthermore, the groundwater level surfaces at T 1 and T 2 are functions of ( x , y ), which may be inferred using the electrical resistivity imaging method (Chang et al, 2017; Rayner et al, 2007).…”
Section: Methods For Determining Aquifer Specific Yield By Gravity Ch...mentioning
confidence: 99%
See 2 more Smart Citations
“…It can be challenging to map the three‐dimensional function of S y ( x , y , z ) in Equation considering aquifer heterogeneity and the high cost of conducting pumping tests over different depths, despite some successes reported in the literature (Tsai et al, 2017; Yeh & Liu, 2000; Zhu & Yeh, 2005). Furthermore, the groundwater level surfaces at T 1 and T 2 are functions of ( x , y ), which may be inferred using the electrical resistivity imaging method (Chang et al, 2017; Rayner et al, 2007).…”
Section: Methods For Determining Aquifer Specific Yield By Gravity Ch...mentioning
confidence: 99%
“…where dv ¼ dxdydz : differential volume change G : gravitational constant (6.67 × 10 −11 m 3 kg −1 s −2 ) ρ w : the water density (¼ 1,000 kg/m 3 ) r : the distance between the gravimeter and the center of the differential volume x, y, z : the three coordinate components of the differential volume x 0 , y 0 , z 0 : the coordinate components of the gravimeter S y (x, y, z) : specific yield It can be challenging to map the three-dimensional function of S y (x, y, z) in Equation 3 considering aquifer heterogeneity and the high cost of conducting pumping tests over different depths, despite some successes reported in the literature (Tsai et al, 2017;Yeh & Liu, 2000;Zhu & Yeh, 2005). Furthermore, the groundwater level surfaces at T 1 and T 2 are functions of (x, y), which may be inferred using the electrical resistivity imaging method (Chang et al, 2017;Rayner et al, 2007).…”
Section: Models Of Groundwater Volume Change and Gravity Change For Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies (Fernández‐Álvarez et al, ; Kennedy et al, , ; Maina & Guadagnini, ; Tsai et al, ) showed that gravity observations in pumping tests, pulse flows, and artificial recharges can provide additional information for estimating hydrogeological parameters such as S s , S y , and transmissivity ( T ) that are related to storage and groundwater flow rate. The geodetic method of S y estimation over small areas or at selected points has been used in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…After a heavy rain stops, the aquifer level can rapidly decline to lower gravity values. We measure such gravity changes and surface deformations to determine hydrogeological parameters critical to understanding aquifer storage capacity and managing groundwater resource.Recent studies (Fernández-Álvarez et al, 2016;Kennedy et al, 2016Kennedy et al, , 2017Maina & Guadagnini, 2018;Tsai et al, 2017) showed that gravity observations in pumping tests, pulse flows, and artificial recharges can provide additional information for estimating hydrogeological parameters such as S s , S y , and transmissivity (T) that are related to storage and groundwater flow rate. The geodetic method of S y estimation over small areas or at selected points has been used in several studies.…”
mentioning
confidence: 99%